2008
DOI: 10.12968/bjon.2008.17.11.29614
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the coexistence of alcohol misuse and depression

Abstract: This article sets out to discuss some issues of this comorbid disorder. Initially the article defines both alcohol misuse and depression and provides indications of symptomatology, many of which overlap. The article identifies that prevalence is high and draws attention to issues of risk, self-harm and suicide. There is a short discussion on causative factors and the article describes the interrelation of these two disorders and goes on to compare the evidence for a cyclic comorbid disorder, where one increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Previous research also reported a similar association between depressive symptoms and problematic alcohol drinking. 26 The results of other studies showed that people having a higher level of negative affect are more likely to engage in harmful alcohol use. 27 Physical activity increased the probability of higher PWB in both genders (data adjusted by sociodemographic, socioeconomic and social factors, depressive symptoms, and CHD).…”
Section: Discussionmentioning
confidence: 97%
“…Previous research also reported a similar association between depressive symptoms and problematic alcohol drinking. 26 The results of other studies showed that people having a higher level of negative affect are more likely to engage in harmful alcohol use. 27 Physical activity increased the probability of higher PWB in both genders (data adjusted by sociodemographic, socioeconomic and social factors, depressive symptoms, and CHD).…”
Section: Discussionmentioning
confidence: 97%
“…6,[21][22][23] According to Watts, most individuals with mood disorders abuse alcohol in search of pleasure and disinhibition or to reduce emotional, behavioral, and cognitive symptoms of depression. 24 However, the state of intoxication induced by alcohol abuse can increase impulsivity and promote thoughts and feelings of hopelessness and sadness, thus worsening mood disorder symptoms. 24 In a recent review, Pompili et al found that mood disorders are frequently precursors of alcohol abuse, but alcoholism may also trigger or exacerbate mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, the state of intoxication induced by alcohol abuse can increase impulsivity and promote thoughts and feelings of hopelessness and sadness, thus worsening mood disorder symptoms. 24 In a recent review, Pompili et al found that mood disorders are frequently precursors of alcohol abuse, but alcoholism may also trigger or exacerbate mood disorders. 10 In our study, mood disorders were associated with alcohol abuse and/or dependence.…”
Section: Discussionmentioning
confidence: 99%
“…These two conditions co-occur at rates greater than chance in community and clinical samples [2,3]. In clinical samples, prevalence of depression in people seeking treatment for AUD ranges from 25.7% [4] to 70% [5].…”
Section: Introductionmentioning
confidence: 99%